2005
DOI: 10.1016/s0753-3322(05)80015-0
|View full text |Cite
|
Sign up to set email alerts
|

Circadian rhythm of maternal blood pressure and fetal growth

Abstract: This study aimed at examining any relation between the circadian variation in blood pressure (BP) in human pregnancy and fetal growth. A prospective study included 52 pregnant women monitored during the third trimester of pregnancy. There were 33 uncomplicated pregnancies with normal fetal growth (Group 1) and 19 pregnancies complicated by intrauterine growth retardation (IUGR), confirmed at birth (Group 2). Ten women (five in each group) had pregnancy-induced hypertension. All women were hospitalized and fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 49 publications
(51 reference statements)
1
11
0
2
Order By: Relevance
“…51 In addition, the non-dipping pattern of circadian BP has been associated with a large increase in cardiovascular morbidity, reflecting an increased risk of target organ damage. 54 Our results showed a decreased melatonin secretion in women with a recent history of preeclampsia and nocturnal hypertension. This finding suggests that melatonin rhythm may be involved with the outcome of women with a history of preeclampsia and nocturnal hypertension.…”
Section: Daytimesupporting
confidence: 50%
“…51 In addition, the non-dipping pattern of circadian BP has been associated with a large increase in cardiovascular morbidity, reflecting an increased risk of target organ damage. 54 Our results showed a decreased melatonin secretion in women with a recent history of preeclampsia and nocturnal hypertension. This finding suggests that melatonin rhythm may be involved with the outcome of women with a history of preeclampsia and nocturnal hypertension.…”
Section: Daytimesupporting
confidence: 50%
“…[2] In contrast, rotating shift work exposure can compromise the health of early middle-aged female workers, [3][4][5] an important population giving birth in industrialized countries. Although studies in some workplace settings have found adverse effects of shift work exposure on reproductive disorders of female employees [6,7] and on birth weight of fetuses, [8,9] few studies have investigated these effects in semiconductor manufacturing factories.…”
Section: Introductionmentioning
confidence: 99%
“…The value of this study is that it illustrates the importance of measuring diagnostic markers of a disease in asymptomatic individuals, so enabling treatment to begin before the disease becomes established (Gupta et al 2008). Also, Maggioni et al (Maggioni et al 2005) studied 52 pregnant women and monitored their BP every 20 min for about 24 h; they showed that, in normotensive individuals, the amplitude of their circadian rhythm of diastolic BP was associated with intrauterine growth retardation and that, in hypertensive individuals, the amplitude of the circadian rhythm of systolic BP was negatively associated with intrauterine growth retardation.…”
Section: Clinical Evidence That Circadian Rhythms Are Implicated In Hmentioning
confidence: 89%